The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.3389/fpls.2016.01845
|View full text |Cite
|
Sign up to set email alerts
|

Glyphosate-Resistant Parthenium hysterophorus in the Caribbean Islands: Non Target Site Resistance and Target Site Resistance in Relation to Resistance Levels

Abstract: Glyphosate has been the most intensely herbicide used worldwide for decades, and continues to be a single tool for controlling weeds in woody crops. However, the adoption of this herbicide in a wide range of culture systems has led to the emergence of resistant weeds. Glyphosate has been widely used primarily on citrus in the Caribbean area, but a study of resistance in the Caribbean islands of Cuba and the Dominican Republic has never been carried out. Unfortunately, Parthenium hysterophorus has developed gly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
46
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(52 citation statements)
references
References 76 publications
(122 reference statements)
5
46
0
Order By: Relevance
“…Control levels attained for the several S populations tested for each Conyza species clearly showed that glyphosate is still a useful herbicide when used as part of an IWM scheme. Control failures are often due to applications at too advanced growth stages or to ignoring environmental factors during herbicide use . Such situations could lead to possible resistance in a few years.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Control levels attained for the several S populations tested for each Conyza species clearly showed that glyphosate is still a useful herbicide when used as part of an IWM scheme. Control failures are often due to applications at too advanced growth stages or to ignoring environmental factors during herbicide use . Such situations could lead to possible resistance in a few years.…”
Section: Discussionsupporting
confidence: 92%
“…In fact, this situation is becoming more common because of selection pressure. However, there are no reports about which mechanism develops first, or how each mechanism individually contributes to the resistance levels exhibited …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result is consistent with previous studies in other glyphosate-resistant rigid ryegrass populations that did not demonstrate any contribution of metabolism to resistance (Fernandez et al, 2015). In fact, glyphosate metabolism does not seem to be a frequent resistance mechanism (Duke, 2011) and, to date, only sourgrass (de Carvalho et al, 2012), horseweed (Gonzalez-Torralva et al, 2012), and ragweed parthenium (Bracamonte et al, 2016) have been described as species able to transform glyphosate into non-toxic compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is plausible to assume that reduced uptake and translocation are the primary causal mechanisms of glyphosate resistance in the studied RG biotype of rigid ryegrass. Lower glyphosate uptake in the RG compared to SG biotype could be explained by structural differences in outer leaf surfaces (Shepherd and Griffiths, 2006; Rojano-Delgado et al, 2012; Alcántara-de la Cruz et al, 2016a), while reduced translocation could result from increased retention of glyphosate in the tips of treated leaves (de Carvalho et al, 2012; Gonzalez-Torralva et al, 2012, 2014; Adu-Yeboah et al, 2014; Bracamonte et al, 2016). …”
Section: Discussionmentioning
confidence: 99%